Internal Control, Governance Risk Management Compliance and Fraud Prevention: The Moderating Role of Good Corporate Governance - Whittleliang Hakki, Tandry; Sofianty, Diamonalisa; Simanungkalit, Jobrinson; Alvionita, Davina (Journal of Accounting and Finance Management, 2025)
The effective implementation of Governance Risk Management and Compliance (GRC) can help companies reduce risks and improve the effectiveness of control, security, and compliance through an integrated and unified approach that reduces the adverse effects of companies related to fraud. This study aims to analyze the influence of Internal Control and Governance Risk Management and Compliance (GRC) on the tendency of fraud in the banking industry. In addition, this study aims to Good Corporate Governance (GCG), and In an effort to understand the extent to which these three factors can prevent fraud, this study uses a quantitative method with a questionnaire survey approach as the main tool for data collection. Respondents in this study are practitioners in the retail industry sector with a target of 170 questionnaires distributed to banking industry companies in the cities of Jakarta, Banten and Bandung. The collected questionnaires are 160 questionnaires and the complete questionnaires that can be processed as data in this study are 153 questionnaires. This research methodology involves the use of statistical test tools SPSS version 26.00. Data analysis is carried out through validity and reliability tests, structural model analysis and prediction testing, as well as the results of hypothesis testing. The results of this study indicate that the influence of Internal Control has a significant and positive effect on fraud prevention actions. While Governance Risk Management Compliance (GRC) does not affect the fraud prevention actions. This study also shows that the role of GCG as a moderator can strengthen the influence of Internal Control, which has a significant and positive effect on fraud prevention actions. While the role of GCG as a moderator cannot strengthen the influence of Governance Risk Management Compliance (GRC) which has a significant and positive effect on fraud prevention actions. The results of this study are expected to contribute to creating a good framework in fraud prevention, such as ensuring that every part of the company runs according to the established goals and helps minimize errors that can lead to fraud, analyzing and mitigating the risks faced by the company.